Stair/escalator/elevator selection behavior of passengers in subway stations based on the fuzzy logic theory. (July 2023) - Zhang, Rui; Yang, Xiaoxia; Zhou, Meiqi; Li, Yongxing; Yang, Xiaoli
The behavior of stair/escalator/elevator selection of passengers at the subway platform could directly affect the travel efficiency and even the service level of the station. This paper proposes a stair/escalator/elevator selection model of passengers at the subway platform, where the cellular automata model is used to simulate passenger movement, and the fuzzy logic theory is used to describe selection behavior. The distance to the stair/escalator/elevator and the density of passengers in front of the facility are selected as the main influence factors. The rationality and effectiveness of the selection model are verified by comparing the field data with simulation results of passengers choosing different stairs/escalators/elevators. The relationship between passenger quantity, passenger speed, escalator quantity, escalator location, and the traffic rate is analyzed based on simulation results, which can provide a theoretical reference for the facility layout optimization at the platform floor of the subway station.